(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Infections triggered by methicillin-resistant Staphylococcus aureus (MRSA) and onset Resistance to significant anxiety in healthcare environments worldwide from vancomycin-resistant Staphylococcus aureus (VRSA).. Aim:To discover Staphylococcus aureus resistant to methacillin and vancomycin by detecting (Mec A ,Van A and Van B) genes by PCR technique. Methods: A total of 250 samples from patients with different clinical cases whom admitted to Hospitals in Al Muthanna province during a period from January 2019 to July 2019. Staphylococcus aureus were isolated and identified by using cultural and biochemical testes.The extracted DNA of isolates were amplified by PCR to detect (mecA, vanA, and vanB) genes. Results: The results showed that 72/ 250 of Staphylococcus aureus isolates contained mecA gene, indicating that all isolates are Methicillin resistant S. aureus (MRSA), only five isolates contained van A gene and only nine isolates contained van B gene. Conclusion: Appropriate monitoring and control measures appear to be crucial to avoid the development and transmission of MRSA and VRSA strains in our nation.